The dual study programme in Germany – concept, strengths and challenges - Hippach-Schneider, Ute [Verfasser] (My University, 2024)
„The first systematic approaches to linking workplace and academic learning developed in Germany in the 1970s. Since then, this form of learning has enjoyed sustained popularity. Institutionally, study programmes have developed in higher education that integrate elements of dual secondary education or adopt them in a modified way. In 2022, 14.2% of all bachelor’s degree programmes were dual study programmes, compared to 10.5% in 2013 (Autorengruppe Bildungsberichterstattung, 2022). Meanwhile, there are different models of dual study programmes. The ways in which practice and theory are linked diverge, some leading to dual qualifications; that is, an academic and a vocational degree. The form of cooperation between higher education institutions and companies is also organised in different ways and varies in intensity. This chapter presents the different models and forms of practice-integrated degree programmes available in Germany and outlines their development. Previous experiences with the different models and their respective strengths and weaknesses are discussed. Finally, by comparing the political approaches to dual study programs in Germany and Switzerland, this chapter provides insight into how countries with strong apprenticeship systems at the secondary level can structure their tertiary education sectors in distinct ways.“ (author‘s abstract; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; 370; Dualer Studiengang; Verzahnung beruflicher und hochschulischer Bildung; Höhere Berufsbildung; Bundesrepublik Deutschland; Schweiz